Heterogeneity of EpCAM-positive cells in low-grade serous ovarian carcinoma ascitic fluid: a clinical case - E. V. Kaigorodova; O. V. Kovalev; A. L. Chernyshova; S. V. Vtorushin; O. V. Shpileva (ABV-press, 2022)
Ovarian cancer is one of the most malignant and aggressive tumors of the female reproductive system. Late diagnosis is one of the most significant problems: more than two-thirds of cases are detected only at stage III-IV. Ovarian cancer is characterized by a unique metastatic process. Implantation is the earliest and most common way of metastasis. It is often accompanied by fluid accumulation in the abdominal cavity, known as ascites. We report a case of low-grade serous ovarian carcinoma with a large heterogeneity of tumor cells in the ascitic fluid detected using multicolor flow cytometry. We demonstrated the advantages and benefits of this method in the diagnosis of ovarian cancer. Multicolor flow cytometry opens new horizons for liquid biopsy in oncology.